Vacation or Validation: Liburan sebagai Bentuk Validasi dan Pencitraan melalui Media Sosial di Kalangan Generasi Z - Asyraf, J. A (JURNAL ILMIAH RESEARCH STUDENT, 2025)
This study aims to identify how holidays and tourism activities are used by Generation Z as a means of self-validation and personal branding through social media. The method used is qualitative descriptive with a social media observation approach and in-depth interviews with participants aged 18–25 who actively publish holiday content on Instagram and TikTok. The results show that the beauty of tourist destinations is no longer judged solely by physical experience, but rather by how "aesthetic" and shareable they are on social media. Social validation in the form of likes and comments has become the primary motivation for tourism activities. This phenomenon also creates unique social pressure among Gen Z, who feel compelled to continuously produce visual content to maintain their digital presence. This research is expected to serve as a reference for understanding the dynamics of digital culture and contemporary tourism.